IMPLEMENTASI VIRTUAL PRIVATE NETWORK (VPN) DENGAN OTENTIKASI RADIUS SERVER PADA PT. ANUGERAH TUNGGAL MANDIRI JAKARTA - Rosmana Rosmana; Fitri Latifah (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2015)
The principle of this research is unavailability of secure data exchange lines, as well as the lack of authentication for users who join the PT network. Anugerah Tunggal Mandiri. To ensure the security of the VPN, the need for an authentication process in which the adoption of restrictions on who is allowed to enter a network. A protocol that supports VPN authentication process on one of which is Service User Authentication Dial-In remote (RADIUS). This protocol is also often used for authentication of the wireless network, Ethernet switches, and other devices. Application of VPN technology allows data exchange can be run safely and smoothly, as supported by the encryption technologies and tunnels. the RADIUS server is used as centralized user management, which has the capacity in terms of authentication, authorization, and accounting. The results showed the data sent through the VPN pass through a special line known as the tunnel name and therefore can not be detected by sniffing program.